Pendampingan Usaha Produksi Keripik Kriouk Lancar Barokah Melalui Legalitas Usaha, E-Commerce, Packaging dan Pembukuan Keuangan - Riskin Hidayat; Septi Alimah; Siti Fatimah (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
The purpose of this community service program are to grow and develop the capabilities of UMKM to become strong and independent businesses. This community service program is in the form of mentoring and facilitating the creation of NIB and PIRT business legality, expanding the marketing network through E-Commerce Shopee and Instagram Business, changing product packaging from ordinary plastic to standing pouch plastic so that it is not inferior to other products that have been circulating in the community, then make a label or business brand as well as financial records. The results of this activity can help increase income for UMKM owners